Pelaksanan Ujian Kompetensi IT dalam meningkatkan kualitas lulusan di SMKN Suak Tapeh Banyuasin - John Roni Coyanda; Desy Iba Ricoida; Dwi Asa Verano (Sekolah Tinggi Ekonomi dan Bisnis Syariah (STEBIS) Indo Global Mandiri, 2023)
Vocational High School (SMK) is a formal education unit that organizes vocational education where the orientation produces graduate students who are ready to work. One area of expertise that is in great demand by students is computer and network engineering (TKJ), where this area of expertise teaches how to make students skilled and competent in the field of computer and network engineering. In this era of digital transformation, computer networks are part of human needs so there are many job opportunities in this field. The purpose of this service and socialization is to increase the understanding and knowledge of SMK students in the field of TKJ in conducting education and preparing themselves to enter the world of work. The partners of this service activity are students of SMKN Suak Tapeh Banyuasin where this activity is carried out in the Computer Laboratory Computer and Network Engineering Study Program. While the method of activity used in this service is planning, directing, guiding and teaching network practicum and conducting competency exams that must be followed before completing education at school. Through this service activity occurs increasing understanding from SMK students majoring in TKJ regarding the areas of expertise they take so as to improve the quality of graduates of SMK N Suak Tapeh and also as a provision to face the world of work. In this era of digital transformation, computer networks are part of human needs so there are many job opportunities in this field. The purpose of this service and socialization is to increase the understanding and knowledge of SMK students in the field of TKJ in conducting education and preparing themselves to enter the world of work. These service partners are students of SMKN Suak Tapeh Banyuasin